Phase transition lowering in dynamically compressed silicon - McBride, E; Krygier, A; Ehnes, A; Galtier, E; Harmand, M; Konôpková, Z; Lee, H; Liermann, H; Nagler, B; Pelka, A; Rödel, M; Schropp, A; et al. (Springer Nature, 2018)
Silicon, being one of the most abundant elements in nature, attracts wide-ranging scientific and technological interest. Specifically, in its elemental form, crystals of remarkable purity can be produced. One may assume that this would lead to silicon being well understood, and indeed, this is the case for many ambient properties, as well as for higher-pressure behaviour under quasi-static loading. However, despite many decades of study, a detailed understanding of the response of silicon to rapid compression—such as that experienced under shock impact—remains elusive. Here, we combine a novel free-electron laser-based X-ray diffraction geometry with laser-driven compression to elucidate the importance of shear generated during shock compression on the occurrence of phase transitions. We observe lowering of the hydrostatic phase boundary in elemental silicon, an ideal model system for investigating high-strength materials, analogous to planetary constituents. Moreover, we unambiguously determine the onset of melting above 14 GPa, previously ascribed to a solid–solid phase transition, undetectable in the now conventional shocked diffraction geometry; transitions to the liquid state are expected to be ubiquitous in all systems at sufficiently high pressures and temperatures.